2012
DOI: 10.1371/journal.pone.0030125
|View full text |Cite
|
Sign up to set email alerts
|

A Bovine Model of Respiratory Chlamydia psittaci Infection: Challenge Dose Titration

Abstract: This study aimed to establish and evaluate a bovine respiratory model of experimentally induced acute C. psittaci infection. Calves are natural hosts and pathogenesis may resemble the situation in humans. Intrabronchial inoculation of C. psittaci strain DC15 was performed in calves aged 2–3 months via bronchoscope at four different challenge doses from 106 to 109 inclusion-forming units (ifu) per animal. Control groups received either UV-inactivated C. psittaci or cell culture medium. While 106 ifu/calf result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(84 citation statements)
references
References 56 publications
(52 reference statements)
6
77
0
1
Order By: Relevance
“…The clinical expression of human psittacosis ranges from flu-like illness to an atypical severe pneumonia (Longbottom & Coulter, 2003). Recent studies demonstrated the ability of C. psittaci to infect bovines with the same tissue tropism as in humans, namely restriction to the respiratory tract and the same outcomes: respiratory tract infection (Reinhold et al, 2012;Ostermann et al, 2013). C. abortus can invade the placenta and lead to abortions or foetal death in the late stage of pregnancy, especially in ruminants.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical expression of human psittacosis ranges from flu-like illness to an atypical severe pneumonia (Longbottom & Coulter, 2003). Recent studies demonstrated the ability of C. psittaci to infect bovines with the same tissue tropism as in humans, namely restriction to the respiratory tract and the same outcomes: respiratory tract infection (Reinhold et al, 2012;Ostermann et al, 2013). C. abortus can invade the placenta and lead to abortions or foetal death in the late stage of pregnancy, especially in ruminants.…”
Section: Introductionmentioning
confidence: 99%
“…Intrabronchial inoculation of a defined amount of the pathogen under videoendoscopic control allows for selective placement of the infectious agent in the lung. This leads to consistent clinical and pathological findings in all animals 34 and allows targeted sampling of lung regions that are expected to be altered due to pathogen exposure.…”
Section: Techniques Applied To and Specimens Obtainable From The Bovimentioning
confidence: 81%
“…In calves, experimental bronchoscopy was described in 1968 for the first time 37 . The intrabronchial application of pathogens was suggested by Potgieter et al as a reliable method to produce lower respiratory tract disease in calves 38 and is now a widespread method in bovine research 34,39,40 . Intrabronchial inoculation of a defined amount of the pathogen under videoendoscopic control allows for selective placement of the infectious agent in the lung.…”
Section: Techniques Applied To and Specimens Obtainable From The Bovimentioning
confidence: 99%
See 1 more Smart Citation
“…Chlamydial EBs were purified by discontinuous density-gradient ultracentrifugation (36) using Visipaque (Nycomed). Purified EBs were stored in sucrose-phosphate-glutamic acid buffer at 280˚C (37). IFU as the measure of infectivity were determined by immunostaining using the IMAGEN kit (OXOID).…”
Section: Chlamydiamentioning
confidence: 99%